Spleen-preserving distal pancreatectomy and lymphadenectomy for glucagonoma syndrome: A case report. Issue 38 (September 2019) - Cao, Xuefeng; Wang, Xixiu; Lu, Yanmin; Zhao, Baolei; Shi, Jian; Guan, Qinghai; Zhang, Xingyuan
Abstract: Rationale: Glucagonoma is a rare type of functional pancreatic neuroendocrine tumor that is characterized by distinctive clinical manifestations; among these, necrolytic migratory erythema represents the hallmark clinical sign of glucagonoma syndrome and is usually presented as the initial complaint of patients. Patient concerns: A 30-year-old male patient was admitted to our hospital with a complaint of diffuse erythematous ulcerating skin rash for more than 10 months. He also complained of hyperglycemia and a weight loss of 15 kg in those months. Diagnosis: This patient underwent a contrast-enhanced computed tomography scan which showed a pancreatic body mass measuring approximately 6 cm with low density accompanied by partial calcification in plain scanning images and uneven enhancement in strengthening periods. In addition, laboratory tests indicated elevated fasting blood glucagon (1109 pg/mL, normal range: 50–150 pg/mL) levels. Glucagonoma syndrome was ultimately diagnosed in clinical. Intervention: Spleen-preserving distal pancreatectomy was conducted and postoperative pathology revealed the presence of glucagonoma. Outcomes: The patient recovered uneventfully with the glucagonoma syndrome disappeared soon after surgery, and the postoperative plasma glucagon decreased to a normal level. Follow-up showed no recurrence for 5 years since the surgery. Lessons: The treatment of glucagonoma should be directed according to the stage at which the disease is diagnosed. Surgery is currently the only method available to cure the tumor, although medications are given to patients who present with advanced glucagonoma and who are not candidates for operation. Multidisciplinary therapy and multimodality treatment are advised, although these have been systematically evaluated to a lesser degree.